The Importance of Science in the Anthology of Lost Works - Rahadini, Astiana Ajeng; Tarasabella, Dhenara Cantika; Ayuani, Kusmira Dwi; Tristanti, Rosy (Green Publisher Indonesia, 2025)
In literature learning, especially geguritan (Javanese poetry), an important factor that influences students’ understanding of meaning is reading comprehension. When students are able to explain the content of a geguritan, it indicates a thorough understanding of the text. However, classroom practice shows that students’ reading comprehension is still lacking. This study aims to describe the widya makna (layers of meaning) in the poetry anthology Gurit Kangen. A descriptive qualitative method was used, with purposive sampling as the sampling technique. The data consist of words, phrases, or clauses containing denotative, connotative, and figurative meanings, which were obtained from documents and informants through document analysis and interviews. Validation techniques include data theory triangulation and methodological triangulation. The data analysis follows Miles and Huberman’s interactive model: data collection, reduction, display, and conclusion. The findings reveal that the widya makna in Gurit Kangen includes denotative, connotative, and figurative meanings. Teachers and students gained new insights into these layers of meaning, particularly denotative, connotative, and figurative meanings, which helped enhance students’ understanding of geguritan.